Digitizing AJN - &NA (AJN, American Journal of Nursing, 2006)
BACKGROUND: Artificial intelligence (AI) can be beneficial in tailoring learning experiences to each student's learning style, needs, and preferences. But the integration of AI into education has also raised a host of concerns, including AI dependency and brain rot. Thus far, there has been limited research on the relationship between the use of AI and brain rot. PURPOSE: This study aimed to explore the relationship between AI dependency and brain rot, specifically among nursing students. METHODS: This mixed-methods study involved undergraduate nursing students at a university in Türkiye. Quantitative data were collected via an online survey that included a sociodemographic questionnaire, the eight-item Brain Rot Scale (BRS-8), and the Dependence on Artificial Intelligence (DAI) Scale. Qualitative data were collected via semistructured interviews. Quantitative data analysis included the use of descriptive statistics, independent samples t tests, one-way analysis of variance, Pearson correlational analysis, and simple linear regression analysis. Qualitative data were analyzed via thematic analysis. RESULTS: A total of 222 nursing students participated in the quantitative phase and 11 also participated in the qualitative interviews. Of the 222 nursing students in the quantitative phase, 90.1% were female; their mean age was 20.63 years. Quantitative analysis found a moderate, positive, and statistically significant correlation between DAI Scale and BRS-8 scores (r = 0.39). Qualitative analysis indicated that students often relied heavily on AI tools in preparing for or taking examinations, with some reporting that the overuse of AI led to reduced focus and dulled thinking. CONCLUSIONS: This study found a moderate, positive, and statistically significant relationship between AI dependency and brain rot among nursing students. The findings indicate that the excessive use of AI tools may contribute to cognitive fatigue and mental exhaustion, and can negatively impact foundational cognitive skills such as critical thinking and decision-making. It is essential that nursing programs ensure the AI literacy of their students and develop a balance of traditional and AI-related pedagogical strategies that best support students' brain functions and cognitive abilities.